Organisational set-up required for efficient field management of irrigation supplies including need for specific irrigation extension services for large irrigation Projects - Vaidya, V.G.; Dixit, D.V. (Journal of Soil and Water Conservation, 2022)
Importance of irrigation to the predominantly agricultural economy of India cannot be over emphasised. Indian Agriculture has mostly to be content with a notoriously capricious rain-fall. Droughts alternating with floods in one or the other part of the country are a common occurrance, causing famine or near-famine conditions, sometimes over extended areas. For successful farming, irrigation in some form is necessary almost throughout the country and particularly in areas where the mean annual rain is 30" and less. Irrigation is virtually indispen-sable for economic use of land. Irrigated farming provides profitable engagement and use almost all the year round both to land and labour, apart from considerably stepping up yields from the same area. it also enables the cultivators to shift from the scarcely—economic dry cropping pattern to one financially more rewarding.